2003
DOI: 10.1002/cne.10596
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the paraventricular nucleus of the thalamus to the rat prefrontal cortex and nucleus accumbens shell: Ultrastructural characteristics and spatial relationships with dopamine afferents

Abstract: The paraventricular nucleus of the thalamus (PVT) participates in the functional integration of limbic cortical and striatal circuitry. In the rat, the PVT projects to the deep layers of the medial prefrontal cortex (PFC) and to the shell of the nucleus accumbens (NAc). However, the synaptic organization of PVT afferents within these regions remains undescribed. Furthermore, although dopamine (DA) modulates excitatory glutamate transmission in both areas, possible anatomic substrates for specific DA modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 59 publications
8
97
0
1
Order By: Relevance
“…This is suggested by known protein-protein interactions between the C-terminals of D1R and the NR1 subunit of NMDA receptor (Lee et al, 2002;Fiorentini et al, 2003;Pei et al, 2004;Pickel et al, 2006). Dopaminergic and glutamatergic terminals converge on the same dendritic spine in the Acb (Sesack and Pickel, 1990;Pinto et al, 2003), where NMDA receptor antagonists also disrupt sensorimotor gating (Mansbach and Geyer, 1989;Bakshi et al, 1999). Interestingly, activation of D2R reduces glutamate release only when the glutamatergic neurons are stimulated at high frequency (Yin and Lovinger, 2006).…”
Section: Apomorphine-and As-induced Changes In D1r Distribution In Thmentioning
confidence: 99%
“…This is suggested by known protein-protein interactions between the C-terminals of D1R and the NR1 subunit of NMDA receptor (Lee et al, 2002;Fiorentini et al, 2003;Pei et al, 2004;Pickel et al, 2006). Dopaminergic and glutamatergic terminals converge on the same dendritic spine in the Acb (Sesack and Pickel, 1990;Pinto et al, 2003), where NMDA receptor antagonists also disrupt sensorimotor gating (Mansbach and Geyer, 1989;Bakshi et al, 1999). Interestingly, activation of D2R reduces glutamate release only when the glutamatergic neurons are stimulated at high frequency (Yin and Lovinger, 2006).…”
Section: Apomorphine-and As-induced Changes In D1r Distribution In Thmentioning
confidence: 99%
“…One of the less-examined major projections is from the paraventricular nucleus of the thalamus (PVT), which, as a subnucleus of the thalamus, lies on the midline just ventral to the third ventricle (Van der Werf et al, 2002;Smith et al, 2004). The PVT projection often converges with other excitatory inputs or midbrain-originated dopaminergic terminals onto the same NAc medium spiny neurons (MSNs; Berendse and Groenewegen, 1990;O'Donnell et al, 1997;Otake and Nakamura, 1998;Pinto et al, 2003;Vertes and Hoover, 2008). This anatomical setup allows the PVT-to-NAc projection to either activate NAc MSNs directly or interact with other inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies of cocaine abusers tested during abstinence and protracted detoxification have reported reduced dopamine (DA) activity (Volkow ND et al, 1997), which has been linked with long lasting decreases in activity of frontal cortical regions [i.e., dorsolateral prefrontal cortex (DLPFC), anterior cingulate gyrus (ACG) and orbitofrontal cortex] (Volkow N et al, 2001). Since the mesocortical DA system facilitates executive function and attention via its projections to the PFC and ACG (Gaspar P, 1992;Goldman-Rakic P et al, 2000), and to the thalamus (Pinto A et al, 2003;Sanchez-Gonzalez M et al, 2005) and DA is necessary for the proper performance of cognitive functions that are modulated by frontal cortical regions (Nieoullon A, 2002), we hypothesized that cocaine abusers tested during abstinence would have significant disruptions in the pattern of corticolimbic activation underlying the performance of these cognitive tasks. It has been previously hypothesized that frontal abnormalities may underlie the disruption in cognitive functioning in cocaine abusers during abstinence and detoxification (Bolla K et al, 2000;Kufahl P et al, 2005); however, this association has not been widely documented using functional magnetic resonance imaging (fMRI).…”
Section: Introductionmentioning
confidence: 99%